Bubka vs. Lavillenie: a comparative analysis - Bussabarger, D. (Track Coach, 2015)
It has long been presumed that the primary reason vaulters can grip higher on fiberglass poles is because the bending of the pole shortens the axis of the pole and therefore reduces the effective handgrip of the vaulter during the first half of the vault. Having done a great many spatially accurate sequence drawings of vaulters (done from film or photo sequences), I have developed an alternative explanation which I think is more relevant. That is, fiberglass poles allow the vaulter`s point of hand grip and his center of gravity (cg), or hips, to follow a lower, less steep path of movement during the first half of the vault vs. stiff poles. This, in turn reduces gravitational resistance against the movement of the vaulter`s point of hand grip and his cg/hips, which conserves the vaulter`s forward momentum. The Petrov/Bubka model believes that the vaulter should emphasize rotating the pole towards vertical like a stiff pole. The problem with this idea is that it creates a higher, steeper path of movement in the vaulter`s point of grip and his cg/ hips. Therefore it increases gravitationa resistance in the critical first half of the vault. This is easily seen by comparing Bubka with Lavillenie. I contend that only an extremely fast vaulter like Bubka, can achieve success by emphasizing rotating the pole towards vertical.